ANALISIS KAIDAH TAFSIR MUFRAD, JAMAK, DAN DHAMIR DALAM REDAKSI AL-QURAN - Zahra Nafisah; Mawaddah; Muhammad Arief Abdillah; Ahmad Dasuki (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study analyzes the principles of tafsir related to mufrad (singular), jamak (plural), and dhamir (pronouns) in the redaction of the Qur'an. These linguistic elements play an important role in understanding the meaning and interpretation of Qur'anic verses. The objective of this research is to explain how the use of singular, plural, and pronouns in the Qur'an influences the interpretation of verses and provides deeper insight into the intended meaning. This study uses a qualitative approach through literature review by examining classical and contemporary works of Qur'anic exegesis and Arabic linguistic studies. The results show that the use of mufrad and jamak forms in the Qur'an often carries specific rhetorical and contextual meanings, while dhamir functions to maintain cohesion, emphasize meaning, and sometimes indicate general or specific references. Understanding these linguistic patterns helps interpreters avoid misinterpretation and reveals the depth and precision of Qur'anic language. Therefore, mastery of these tafsir principles is essential for scholars and students in comprehending the Qur'an accurately and contextually.